Respostas

A melhor resposta!
2014-03-16T20:49:39-03:00
10x - 8 - 2 = 7x - 4
10x - 7x = -4 + 8 + 2
3x = 6
X = 2

2x + 5 - 5x = - 13
-3x = -13 -5
-3x = - 18
3x = 18
x = 6

4x -4 -5x = -6 + 90
4x -5x = -6 +90 + 4
-1x = 88
X = -88

-3x +10 = 2x +81
-3x -2x = 81 -10
-5x = 71
-x = 71/5
X = -(71/5)

3x -4=11
3x = 11 + 4
3x = 15
x = 5
4x + 6 = 12 -2x
4x +2x = 12 - 6
6x = 6
x = 1

X - 10 -8 = 2x + 4
x -2x = 4 +8+10
-x = 22
X= -22

5x + 4x -10 = 2x -2
5x -2x +4x = -2 +10
7x = 8
X=8/7
Espero que eu tenha ajudado. Bjs
2 5 2